APLIKASI MODEL DIRECT INSTRUCTION AND COLLABORATIVE LEARNING MELALUI LESSON STUDY UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA MEMBUAT MEDIA PENDIDIKAN KIMIA BERBASIS KOMPUTER - Syahmani Syahmani; Rusmansyah Rusmansyah (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2010)
Abstract: Implementation of computer-based media at teaching and learning by using Direct Instruction and Collaborative Learning's model (DI-CL) was conducted. This study addresses to find out student’s improvement of cognitive skill, physicomotoric skills, and respon to the DI-CL model via lesson study. This action research class that were invoved 37 students found that the category of student’s acvhiements on designing computer-based media are 25% excelent, 66,7% good, and 8,3% medium. Student’s comprehention increased from 51,36% on the first cycle to 100% on the fourth cycle. Generally, the media quality designed by students in good category. Meanwhile, design, animation, and graphic need to be increased. Students gave a positive respond to the model which implemented in this teaching and learning process. The implementation of DI-CL model improves the students learning autonomy and their capability seen from the organization of ideas, interactivity and efectivity.Key word: Direct Instruction and Collaborative Learning's model, Lesson Study, computer-based media,learning autonomy